Der Marsch zum Führer: documentary films and newsreels in the indoctrination of youth in Nazi Germany - Almeida Aguiar, Antonio (Historia y Memoria de la Educación, 2022)
Documentaries and educational newsreels have only begun to constitute an area of ​​research in Spain in recent years. From this perspective, our article aims to contribute to the analysis of documentaries as well as the mechanisms used by the Nazi regime for the promotion of certain educational ideals, both formal and non-formal, with the clear objective of indoctrinating the country’s youth. In addition to highlighting the propagandistic instrumentation of cinematography as a fundamental part of education in the interior of the country and beyond its borders, we analyze the role of the Hitlerjugend and Bund Deutscher Mädel in the mechanisms used for indoctrination. To substantiate this discourse, we have carried out a study based on primary sources, both film and text. These include, on the one hand, the documentary Der Marsch zum Führer, as well as the Junges Europa and NO-DO news programs. On the other hand, we examine the network of instruments that controlled the formation of youth and that relied on books and journals with speeches that reflected the visual materials worked on: works such as Marschtritt Deustschland and the Junges Europa journal. The results feature characteristics, in the form of both visual symbols and textual content, that coincide with the typical educational elements of European totalitarianism.